Portrait continuing education Germany - Nuissl, Ekkehard [Verfasser]; Pehl, Klaus [Verfasser] (Bertelsmann, 2004)
"This third edition of the DIE Portrait Continuing Education in Germany has been extensively revised to include up-to-date figures on such key areas of continuing education as numbers of courses offered, participants, institutions and staff employed. The volume also outlines the history of German adult education and provides information on its basis in law and funding matters. Educational researchers, planners, administrators and practitioners, will thus obtain a thorough insight into the continuing education system in Germany and current and future developmental trends." (Publisher, BIBB-Doku)
Keywords: Erwachsenenbildung; Deutschland